Septohippocampal acetylcholine and theta oscillations can modulate memory encoding and retrieval: Insights from a neural masses network - Gabriele Pirazzini; Mauro Ursino (Brain Research Bulletin, 2025)
The hippocampus' ability to encode new information while simultaneously avoiding disruptive interference poses a fundamental challenge to cognitive neuroscience. It has been supposed that dynamical changes in acetylcholine (ACh), a neurotransmitter involved in learning and memory, can facilitate a shifting between encoding and retrieval: high ACh levels promote encoding by enhancing synaptic plasticity while concurrently suppressing retrieval-related networks; low ACh levels favor retrieval, suppressing external inputs and synaptic potentiation. The primary source of ACh in the hippocampus, the medial septum/diagonal band of Broca, is also a key determinant of hippocampal theta: these two aspects could therefore be integrated, with ACh and theta fluctuations modulating encoding and retrieval phases. Here, we present a computational model based on neural masses, simulating the possible role of ACh on hippocampal function. A first set of simulations was performed assuming that ACh’s dynamics are comparable to those of theta. Simulations support the hypothesis that ACh can orchestrate encoding and retrieval at different phases of the theta cycle, but they require an ACh time constant of the order of a few milliseconds, which is much faster than that currently measured. A second set of simulations considers the effect of a slower ACh time scale. Moreover, the network isolated from the environment with constant low ACh levels, spontaneously retrieves stored information, offering early insights into the hippocampal role during states such as imagination, rumination, and slow-wave sleep. Finally, sensitive analysis of model parameters may elucidate the pathophysiology of mnemonic disorders characterized by cholinergic dysfunction, like dementia and amnesia.